Socially engaged art education: defining and defending the practice - Schlemmer, Ross H (Handbook of Research on the Facilitation of Civic Engagement through Community Art, 2017)
Community Arts have a long history within art and education, yet its practices continue to evolve. The issue of nomenclature when discussing such socially engaged practices raises the deeper questions of whether work in this area suggests the formalization of yet another new genre of art, or does it entail a more profound re-ordering of the discursive system that underlies most existing modes of artistic production? This chapter attends to individual differences and similarities in perception and practice through a careful consideration for how the field of art education might nurture new and diverse articulations of community-based practices that emphasize relational aesthetics, participatory pedagogy, and socially engaged artistic practices. This chapter will (re)frame the discourse as Socially Engaged Art Education (SEAE) to emphasize a new terrain of consciousness that is socially responsible and ethically sound, and goes beyond mere promotion of aesthetic quality to contribute to improved quality of life.
Citation Key Alias: lens.org/014-957-936-013-626
Keywords: dept.art

Socially engaged art education: practices, processes, and possibilities - Schlemmer, Ross H.; Carpenter, B. Stephen; Hitchcock, Erika (Art Education, 2017)
7 citations (Crossref) [2023-10-31] Citation Key Alias: pop00121
Keywords: dept.art; peer-reviewed